-4x+7-6x-8=43

Simple and best practice solution for -4x+7-6x-8=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+7-6x-8=43 equation:



-4x+7-6x-8=43
We move all terms to the left:
-4x+7-6x-8-(43)=0
We add all the numbers together, and all the variables
-10x-44=0
We move all terms containing x to the left, all other terms to the right
-10x=44
x=44/-10
x=-4+2/5

See similar equations:

| 3/4(x-16)=0 | | 5–-z=2 | | 18x-160=x-110 | | 12-4y=64 | | -8w+35=-3w+5 | | 1.1n=+1.5n-5.6=-16 | | -1+3x=-2x+54 | | 8(w+7)=2w+38 | | 4/9m=22 | | 10–2x=-5x–50 | | -10=n+8 | | 6x–15=8=-15 | | 18x-160=x+110 | | -5(x+6)-3=-18 | | z+2=4z-7 | | 3x2-4x+8=0 | | -4x+7-2(3x-4)=-43 | | 4x+14=−10 | | A(7x)+B(x+17)+C(x+28)=180 | | 3/4p=27 | | 1/4+2/3x=11/12 | | 10y-12+37=180 | | 3x=2x=15 | | -3+16-5s=13-s | | 5x–20=100 | | 12x+25-3(x+8)=38 | | 5(3x-7)=18 | | 3(3x-4)+2=14 | | 13x-8=-10x+15 | | 1.5(2.5+2x)=-2x+5.5 | | 1+3v=9+2v* | | 1/6=w/18 |

Equations solver categories